STUDY OF THEORETICAL AND EXPERIMENTAL ASPECTS OF FLUID MOTION THROUGH PLASTICALLY DEFORMABLE POROUS MEDIA AS AN APPLICATION TO OILSEED EXTRACTION PROCESS BY THE SCREW PRESS - Slavnov, E.V.; Skul’skiy, O.I.; Petrov, I.A.; Anferov, S.D.; Sudakov, A.I.; Shakirov, N.V. (Perm Federal Research Centre Journal, 2017)
The paper presents the results of an experimental and theoretical investigation of fluid motion through plastically deformable porous media during oilseed extraction process by the screw press. It is shown that filtering properties change significantly due to bulk concentration and pressure. The influence of loading rate on the process of oil extraction is analyzed. The minimum residual oil content is evaluated. Some aspects concerning mathematical modeling of the examined process are discussed.